Post-stroke Fatigue and Depressive Symptoms Are Differentially Related to Mobility and Cognitive Performance - MacIntosh, Bradley J.; Edwards, Jodi D.; Kang, Mani; Cogo-Moreira, Hugo; Chen, Joyce L.; Mochizuki, George; Herrmann, Nathan; Swardfager, Walter (Frontiers in Aging Neuroscience, 2017)
Background: Fatigue and depressive symptoms are common and often inter-related stroke sequelae. This study investigates how they contribute, directly or indirectly, to mobility and cognitive outcomes within 6 months of stroke. Methods: Participants were recruited from 4 stroke centres in Ontario, Canada. Post-stroke fatigue was assessed using the Fatigue Assessment Scale (FAS). Depressive symptoms were screened using the Center for Epidemiological Studies Scale for Depression (CES-D). Factor analyses were used to construct scores from mobility (distance travelled during a 2-minute walk test, Chedoke-McMaster Stroke Assessment leg score [CMSA-leg], and Berg Balance Scale [BBS] total score) and cognitive (Montreal Cognitive Assessment [MoCA], Trail-Making Tests A and B, and five-word free recall) tests. Direct associations were assessed in linear regression models and indirect effects were assessed in path models. Covariates were age, sex, education, antidepressant use, days since stroke and stroke severity. Results: CES-D and FAS scores were highly correlated (r>0.51, p<0.0001). Depressive symptoms were associated with cognition (β=-0.184, p=0.04) and indirectly with mobility, mediated by fatigue (indirect effect = -0.0142, 95% CI: -0.0277 to -0.0033). Fatigue was associated with mobility (β=-0.253, p=0.01), and indirectly with cognition, mediated by depressive symptoms (indirect effect = -0.0113, 95% CI: -0.0242 to -0.0023). Conclusions: Fatigue and depressive symptoms contribute distinctly to cognitive and mobility impairments post-stroke. Fatigue was associated with poorer lower limb motor function, and with cognition indirectly via depressive symptoms.